UPAYA PROTOKOL DAN KOMUNIKASI PIMPINAN KOTA BANDUNG DALAM MENYAJIKAN INFORMASI MELALUI MEDIA SOSIAL INSTAGRAM @HALOBANDUNG - Sean Aileen Hasyna; Raka Rizca Haqqu (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
This research is titled "Efforts of the Protocol and Communications of the Leadership of Bandung City in Presenting Information through the Instagram Social Media Account @halobandung." The main objective of this study is to describe and analyze the efforts made by the Protocol and Communications of the Leadership of Bandung City (Prokopim) in presenting information through the Instagram account @halobandung. This research uses a qualitative descriptive approach to understand the phenomena of communication, collaboration, education, and entertainment implemented by Prokopim. Social media, especially Instagram, has become an important communication tool for the Bandung City Government to interact with the public. Through content analysis and interviews with six informants, this study found that Prokopim has successfully implemented an effective communication strategy by conveying information related to government activities, collaboration with other agencies, as well as education through relevant and entertaining content. The Instagram account @halobandung also shows consistency in content management and is able to increase public engagement. The main findings of this study indicate that Prokopim has utilized four pillars of social media strategy, namely communication, collaboration, education, and entertainment, in presenting information. This strategy not only successfully increases interaction with the public but also builds awareness and public participation in various government programs. This research is expected to serve as a reference for other government agencies in optimizing the use of social media for effective public communication.